Employee Recruitment Decision Support System at Royal Prima Hospital Using the SAW Method - Muhammad Abduh Al-Bathani; Irfan Nainggolan; Lilis Suryani; Achmad Riyan Hadiyatma; Muhammad Irfan Syarif (Bahasa Indonesia, 2026)
The employee recruitment and selection process is a strategic stage in human resource management because it directly influences the quality and performance of the organization. Problems that often arise in this process are subjectivity of assessment, inaccuracy of candidate selection, and limitations in processing multiple criteria simultaneously. This study aims to analyze and support the decision-making process in employee recruitment and selection by utilizing a competency-based decision support system. The method used is a descriptive-analytical approach with the application of a multi-criteria decision-making model to evaluate prospective employees based on the criteria of education, work experience, skills, and work attitudes. The results of the study indicate that the application of a decision support system can assist management in producing more objective, systematic, and transparent decisions. Thus, this system is expected to improve the effectiveness and efficiency of the employee recruitment and selection process in the organization.